2023
DOI: 10.32615/ps.2022.039
|View full text |Cite
|
Sign up to set email alerts
|

Moderate photoinhibition of PSII and oxidation of P700 contribute to chilling tolerance of tropical tree species in subtropics of China

Abstract: electron flow through PSI; ETR(II) -photosynthetic electron flow through PSII; Fd -ferredoxin; Fv/Fm -maximum quantum yield of PSII in the dark-adapted state; gs -stomatal conductance; LEF -linear electron flow; NPQ -nonphotochemical quenching; P680 -chlorophyll a of PSII reaction centers; P680 + -oxidized P680; P680* -excited P680; P700 -chlorophyll a of PSI reaction centers; P700 + -oxidized P700; P700* -excited P700; PC -plastocyanin; Pm -maximum photooxidizable P700; PN -net photosynthetic rate; PQ -plasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 78 publications
0
0
0
Order By: Relevance
“…It has been reported that proline plays a protective role in plants exposed to diverse stresses and is thought to be acting as a cellular osmotic regulator. And along with other enzymatic and non-enzymatic ROS quenching mechanisms proline regulates increased ROS production due to the reduced light-dependent and CO 2 assimilation reactions of photosynthesis ( Munns and Tester, 2008 ; Aycan et al., 2022 ; Singh et al., 2022 ; Sunoj et al., 2022 ). A study reported the genotypic differences in proline accumulation under salinity were seen in wheat genotypes ( Tavakoli et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that proline plays a protective role in plants exposed to diverse stresses and is thought to be acting as a cellular osmotic regulator. And along with other enzymatic and non-enzymatic ROS quenching mechanisms proline regulates increased ROS production due to the reduced light-dependent and CO 2 assimilation reactions of photosynthesis ( Munns and Tester, 2008 ; Aycan et al., 2022 ; Singh et al., 2022 ; Sunoj et al., 2022 ). A study reported the genotypic differences in proline accumulation under salinity were seen in wheat genotypes ( Tavakoli et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The research by Sunoj et al (2023) reports the effects of chilling on photosynthesis in six tropical tree species growing in the subtropics in China. The authors found that chilling induced stomatal and nonstomatal effects and photoinhibition of PSII, with severe effects in Ixora chinensis.…”
mentioning
confidence: 99%